Discretionary Principles of Management: Justification of Practical Application in the Customs Service - Anatolievich Ostanin, Vladimir; Aleksandrovich Kosenko, Viktor; Vladimirovna Glukhova, Zlata (International Journal of Engineering and Technology, 2018)
In the context of globalization and internationalization of economic relations, there is an active development of customs services, in which regulation of a certain part of the customs service moves to the international level. The quality of services provided by the customs authorities influences not only the time needed to complete customs formalities, but also the financial risks and costs of all participants involved in foreign economic activity. The increasing foreign trade turnover requires improvement of the movement and processing mechanisms of goods and services across the customs border of the Russian Federation, which necessitates the active implementation of new services and technologies of customs clearance. Customs service is understood not only as a public service performed by public authorities, but also as a specific type of activity aimed at facilitating the implementation of foreign economic operations carried out by commercial organizations of the customs sphere.Â Â